Webrooming and Pure Online Shopping Behavior of Skincare Consumers in Indonesia - Sayyida; Hartini , Sustri; Singh , Sanju Kumar (Journal of Innovation in Academia, 2025)
Based on social cognitive theory, this study examines the influence of content marketing and electronic word-of-mouth (e-WOM) on the purchasing decisions of skincare consumers. It also investigates whether the effects of content marketing and e-WOM on purchasing decisions differ significantly between pure online shoppers and webroomers. A quantitative approach was used to examine the causal relationship among the study variables. Likewise, cross-sectional data were purposively collected from 298 skintific users in Sumenep Regency, Indonesia. SmartPLS 4.0 was employed for analysis. This study found that both content marketing and e-WOM significantly influence skincare purchasing decisions, with no notable difference between pure online shoppers and webroomers. The results suggest that digital content and peer-generated reviews have become central touchpoints in high-involvement product decisions, transcending the physical-digital shopping divide. Findings reveal converging digital consumer behaviors, urging brands to adopt consistent, credible, and engaging digital strategies to build trust and drive purchase intentions.